R-curve behavior of a short-fiber reinforced resin composite after water storage - Tiu, Janine; Belli, Renan; Lohbauer, Ulrich (Journal of the Mechanical Behavior of Biomedical Materials, 2020)
As a supplement to our investigation into R-curves in a short-fiber reinforced dental resin composite, we investigate the effects of 2-months water storage. Water is known to degrade the siloxane bonds linking matrix and fillers, which has been suggested to decrease the fracture toughness in conventional resin composites. However, fiber-reinforced systems seem to be less affected as the toughness is dependent on fiber bridging, which is only effective if a weaker interfacial bond between fiber and matrix is present.
CRIS-Team Scopus Importer:2020-02-21